Comparing the Disease Severity in Iraqi Psoriasis Patients According to Some Immunological and Biological Factors - Sabri , Samara A.; Ibraheem, Shaima R. (Iraqi Journal of Science, 2023)
Psoriasis is a chronic inflammatory skin disease that is closely related to the oxidative stress state of the body. The current study focused on some immunological indicators directly related to inflammation (Procalcitonin, and lysozyme) with the aim of investigating their potential as a prognostic factor for psoriasis. This study included 150 samples, including 90 patients with psoriasis and 40 people who appeared to be healthy, and was conducted from November 2021 to April 2022. The results showed a significant increase in the level of procalcitonin in patients with psoriasis compared to its level in the control group, while it was noted that the increase in the level of the other indicators was not significant, according to the statistical study. It was found that the highest percentage of psoriasis patients are those with excessive weights, and they constitute 37.8 %, and in the second degree they are obese, and they form 35.6 %, and a large percentage 62.2% of the patients have a family history of as a risk factor, and a percentage of 18.9 of the patients are smokers and the same percentage 18.9% of patients are diabetes, while those who suffer from hypertension accounted for 12.2%. All these indicators showed significant differences compared to the control group. It was also found that the value of the disease severity index in hypertensive patients is lower than that in normal pressure psoriasis patients. This result indicates that there is no association between both disorders. Although the increase in lysozyme level in psoriasis patients is not significant when compared to its level in healthy subjects, its level in smoking psoriasis patients was significantly higher than its level in non-smokers psoriasis patients, and this result indicates the role of smoking in raising the level of this inflammatory marker. It was found that the highest level of procalcitonin (457.79 ± 256.75) pg/ml was in patients over 50 years of age, and the lower the age, the lower the level of procalcitonin. This result confirms the relationship between age and severity of inflammation, the older you get, the greater the inflammation, In addition, there are other inflammatory indicators that were not mentioned in this study.